Then again, maybe I won't : a novel - Blume, Judy. (New York, N.Y. : Dell Pub., 1987)
Thirteen-year-old Tony Miglione faces many new problems when his family moves to a swanky Long Island community.
Originally published: Scarsdale, N.Y. : Bradbury Press, 1971.
590
Accelerated Reader AR
Keywords: Adolescence -- Fiction